2015
DOI: 10.6023/cjoc201410041
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Antifungal Activity of Novel 3-[(5-Benzylthio- 1,3,4-oxadiazol-2-yl)methyl]benzo[d]thiazol- (oxazol)-2(3H)-ones

Abstract: In order to find novel biologically active pesticide lead compounds, twenty-one novel 3-[(5-benzylthio-1,3,4-oxadiazol-2-yl)methyl]benzo[d]thiazol(oxazol)-2(3H)-ones were synthesized by 2-benzothiazolinone/benzoxazolone as starting materials via substitution, hydrazine, cyclization and the last benzylation reaction. The structures of the title compounds were characterized by 1 H NMR, IR, EI-MS and elemental analysis. The preliminary bioassay results indicated that most of them showed moderate inhibition activi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 6 publications
0
2
0
Order By: Relevance
“…In addition, the preliminary bioassay showed compound 25 (Figure 5) had a good antifungal activity (100%) against P. cubensis at 100 μg/mL, which was equal to that of Fluazinam. In the same year, Ruan and coworkers [37] reported a series of novel thioether derivatives containing a 1,3,4-oxadiazole moiety and evaluation of the bioactivities against C. orbiculare, B. cinerea, and R. solani at 50 μg/mL, and the best inhibition rates of compound 26 against B. cinerea reached 86.12%, which was even better than that of Propiconazoleg6.…”
Section: Antifungal Activitymentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, the preliminary bioassay showed compound 25 (Figure 5) had a good antifungal activity (100%) against P. cubensis at 100 μg/mL, which was equal to that of Fluazinam. In the same year, Ruan and coworkers [37] reported a series of novel thioether derivatives containing a 1,3,4-oxadiazole moiety and evaluation of the bioactivities against C. orbiculare, B. cinerea, and R. solani at 50 μg/mL, and the best inhibition rates of compound 26 against B. cinerea reached 86.12%, which was even better than that of Propiconazoleg6.…”
Section: Antifungal Activitymentioning
confidence: 99%
“…The structures of compounds [36][37][38][39] In 2020, a series of structurally novel 1,3,4-oxadiazole thioether derivatives (46-48, Figure 10) were designed and synthesized by Shi et al [57] and Song et al [58], and bioassay results showed that compound 46 revealed better activity against G. zeae (61.6%), which was superior to that of Hymexazol, compound 47 displayed the best bioassay against U. viciae-fabae (77%) at 100 μg/mL than those of Streptochlorin and Pimprinine, and compound 48 had an inhibitory rate (99%) at 20 μg/mL against P. dissimile, which was equal to that of Streptochlorin. Hua et al [59] synthesized a series of novel thioether derivatives bearing a pyridine moiety and evaluated for their in vitro fungicidal activities against G. zeae, R. solani, C. circumscissa, P. piricola, A. kikuchiana, B. cinerea, C. capsici, and P. melongenae.…”
Section: Antifungal Activitymentioning
confidence: 99%